2009
DOI: 10.1093/molbev/msp046
|View full text |Cite
|
Sign up to set email alerts
|

Differences in DNA Methylation Patterns and Expression of the CCRK Gene in Human and Nonhuman Primate Cortices

Abstract: Changes in DNA methylation patterns during embryo development and differentiation processes are linked to the transcriptional plasticity of our genome. However, little is known about the evolutionary conservation of DNA methylation patterns and the evolutionary impact of epigenetic differences between closely related species. Here we compared the methylation patterns of CpG islands (CGIs) in the promoter regions of seven genes in humans and chimpanzees. We identified a block of CpGs in the cell cycle-related k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 53 publications
1
42
0
Order By: Relevance
“…With few exceptions, however (e.g., with respect to DNA methylation; Farcas et al 2009), comparative studies in primates have not explored the extent to which epigenetic differences between species underlie interspecies differences in gene regulation. To take first steps toward this goal, we compared gene expression levels and histone modification data in samples from humans and two of our closest extant evolutionary relatives, chimpanzees (Pan troglodytes) and rhesus macaques (Macaca mulatta).…”
Section: Omparative Studies Of Gene Expression Havementioning
confidence: 99%
“…With few exceptions, however (e.g., with respect to DNA methylation; Farcas et al 2009), comparative studies in primates have not explored the extent to which epigenetic differences between species underlie interspecies differences in gene regulation. To take first steps toward this goal, we compared gene expression levels and histone modification data in samples from humans and two of our closest extant evolutionary relatives, chimpanzees (Pan troglodytes) and rhesus macaques (Macaca mulatta).…”
Section: Omparative Studies Of Gene Expression Havementioning
confidence: 99%
“…These epigenetic changes can also have a lasting impact since changes in maternal diet can affect methylation status for multiple generations (reviewed in [98]). Two preliminary studies of methylation change between humans and chimpanzees noted significant differences in methylation patterns, with a higher amount of methylation seen in humans [99,100]. Dietary changes incorporating more sources of methyl groups (e.g.…”
Section: Other Shifts In the Genomic Landscape Owing To Dietary Shiftsmentioning
confidence: 99%
“…Recent comparative studies of certain epigenetic modifications in primates provide further support for the association between epigenetic modification variation and gene expression variation [23][24][25]39]. For example, Pai et al showed that inter-species differences in DNA methylation pattern correlate with differences in gene expression level across species [24], and Cain et al found that inter-species differences in the profile of the histone modification H3K4me3 are associated with changes in gene expression level between species [25].…”
Section: Introductionmentioning
confidence: 97%
“…However, we still know little about the underling regulatory mechanisms leading to the differences in gene expression levels across species. In particular, although a few studies have shown that the inter-species differences in certain epigenetic mechanisms can explain (in a statistical sense) a small proportion of variation in gene expression levels between species [23][24][25], the relative importance of evolutionary changes in different epigenetic regulatory mechanisms remains largely elusive.…”
Section: Introductionmentioning
confidence: 99%